Analisis manajemen strategi Bank Muamalat Indonesia: Upaya memperkuat posisi pasar di tengah persaingan industri keuangan syariah - Priyambodo, Alvin Dwi (Maliki Interdisciplinary Journal, 2025)
This study aims to analyze the management strategies implemented by Bank Muamalat Indonesia (BMI) in strengthening the market position in the midst of competition in the Islamic finance industry for the 2020–2025 period. The method used was a literature review of 18 empirical studies and official sources related to corporate strategy, risk management, digital transformation, and human resource management. The results show that BMI implements a multi-dimensional strategy that includes four main pillars: digitalization-based operational efficiency, sharia product innovation, consolidation of governance and risk management, and work culture reform through human resource strengthening. At the operational level, work discipline and motivation factors are the main determinants of employee performance, while at the corporate level, digital innovation and product differentiation are the main instruments for increasing competitiveness. This integrative strategy contributes to improving customer reputation and loyalty, while strengthening the application of Good Corporate Governance principles and Islamic values in organizational governance. This study recommends the need for further analysis of the long-term impact of digitalization and risk reform on BMI’s market share and financial performance.